Hubungan Dukungan Suami Terhadap Status Anemia Pada Ibu Hamil Di Puskesmas Sengkol Kabupaten Lombok Tengah - Hardaniyati, Hardaniyati; Ariendha, Dian Soekmawaty Riezqy (Jurnal Kesehatan Qamarul Huda, 2018)
The purpose of this study was to determine the relationship of husband's support to anemia status in pregnancy at Sengkol Health Center, Central Lombok Regency. This research method is a cross sectional observational study. It was conducted in March-April 2018 with an anemia random sampling population of 59 respondents, data analysis using univariate analysis, bivariate analysis using chi square. the results showed that there was a relationship between husband's support and anemia status, most respondents did not support moderate anemia 19 (63.3%), the results of the analysis using chi-square obtained p-value 0.002 due to p-value <? (0.05) . Husband's support from the family can encourage pregnant women to be more enthusiastic in facing the changes that occur during pregnancy, including maintaining the health of their pregnancy through increased pregnancy visits and consumption of iron tablets. In conclusion, there is a relationship between husband's support for anemia status in pregnant women in Sengkol Health Center, Central Lombok District